Pengaruh Blansir dan Tween 80 pada Pengeringan Busa terhadap Karakteristik Serbuk Seledri - Faleh Setia Budi; Harum Fadhilatunnur; Dhiorama Akbar Novandra (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Instant powder drinks are gaining popularity due to their practicality, durability, and ease of storage. As a result, fresh celery was converted into instant celery powder. The foam-mat drying technique was utilized to produce the celery powder because of its low drying temperature of 60°C and relatively fast drying process. To prevent food deterioration and enhance the characteristics of celery powder, the blanching process was employed. Tween 80 was also used to produce foam, which facilitated the foam mat drying process of celery. This study aimed to examine the impact of blanched or un-blanched treatment and the concentration of tween 80 on the physical and chemical characteristics of celery powder. The experiment used a completely randomized design with two factors, namely blanching treatment and the concentration of tween 80 (0.1%, 0.5%, 1.0%). Yield, water content, solubility in water, antioxidant activity, total phenol, and yield of celery powder were tested. The results indicated that increasing the concentration of tween 80 had a positive effect on the yield, solubility, antioxidant activity, and total phenols of celery powder products, but had a negative impact on the moisture content of the product. The treatment of un-blanced/blanching had a positive effect on the solubility, antioxidant activity, and total phenol of the product but a negative impact on the yield and moisture content of the product. The best celery powder product was produced by treating it with blanching and tween 80 concentration of 1%. It had the following characteristics: solubility of 93.87±0.28%, antioxidant activity of 251.22±4.67 mg AEAC/100 g, phenolic total of 77.44±2.80 mg GAE/100 g, and moisture content of 4.59±0.02%. The yield of celery powder obtained was 12.38±0.2%.